Respuesta :
f(x) = 0.5(1 - x)
f(-1) = 0.5(1 - (-1))
= 0.5(2)
= 1
answer B
HOPE I AM THE BRAINLIEST I NEED IT
f(-1) = 0.5(1 - (-1))
= 0.5(2)
= 1
answer B
HOPE I AM THE BRAINLIEST I NEED IT
Answer:
[tex]f(-1)=1[/tex]
Step-by-step explanation:
If [tex]f(x) = 0.5(1 - x)[/tex], find the value of f(-1)
we are given with function [tex]f(x) = 0.5(1 - x)[/tex]
To find f(-1) we plug in -1 for x in f(x)
[tex]f(x) = 0.5(1 - x)[/tex]
[tex]f(-1) = 0.5(1 - (-1))[/tex]
[tex]f(-1) = 0.5(1+1)[/tex]
[tex]f(-1) = 0.5(2)[/tex]
[tex]f(-1)=1[/tex]